2022
DOI: 10.1186/s12894-022-01037-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers for predicting the overall survival outcome of kidney renal papillary cell carcinoma: an analysis of ferroptosis-related LNCRNAs

Abstract: Background Kidney renal papillary cell carcinoma (KIRP) is a dangerous cancer, which accounts for 15–20% of all kidney malignancies. Ferroptosis is a rare kind of cell death that overcomes medication resistance. Ferroptosis-related long non-coding RNAs (LNCRNAs) in KIRP, remain unknown. Method We wanted to express how ferroptosis-related LNCRNAs interact with immune cell infiltration in KIRP. Gene set enrichment analysis in the GO and KEGG database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The study found that 7 different frlncRNAs had strong link to the prognosis of patients with PRCC [16]. The frlncRNAs CASC19, AC090197.1, AC099850.3, AL033397.2, LINC00462, and B3GALT1-AS1 were designated as oncogenes in PRCC, whereas LNCTAM34A and AC024022.1 are recognized as tumor suppressor genes in PRCC [17]. These studies have demonstrated that frlncRNAs are associated with the prognosis of kidney cancers, and play diverse roles in cancer progression.…”
Section: Identification Of Frlncrnas In Kidney Cancermentioning
confidence: 88%
See 1 more Smart Citation
“…The study found that 7 different frlncRNAs had strong link to the prognosis of patients with PRCC [16]. The frlncRNAs CASC19, AC090197.1, AC099850.3, AL033397.2, LINC00462, and B3GALT1-AS1 were designated as oncogenes in PRCC, whereas LNCTAM34A and AC024022.1 are recognized as tumor suppressor genes in PRCC [17]. These studies have demonstrated that frlncRNAs are associated with the prognosis of kidney cancers, and play diverse roles in cancer progression.…”
Section: Identification Of Frlncrnas In Kidney Cancermentioning
confidence: 88%
“…Wu et al found some frlncRNAs targeting inflammation-and immune-promoting genes viz. CD160, TNFSF4, CD80, BTLA, and TNFRSF9 differentially expressed in the high-and low-risk groups with PRCC [17]. It indicates that similar and dissimilar frlncRNAsrelated immune genes were found in different studies, and the accurate molecular functions still needs to further verification.…”
Section: Immune-related Frlncrnas In Urologic Cancermentioning
confidence: 91%
“…There are however, several other lncRNAs in our panel, which are not frequent in similar RCC-focused studies. For example AZGP1P1 has been associated only with prognosis in breast cancer (Liu et al 2019), LINC00462, which has been associated with ferroptosis according to one recent work (Wu et al 2022b), LINC00955 without any other evidence, RMST, which is known to be involved in the development of other tumors, but not RCC (Chen et al 2022) and similarly ZNF667-AS1, also known as MORT (Vrba and Futscher 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Kim et al have shown a relationship between BCR gene expression and RCC [28, 29]. Gene expression of BCR was also upregulated in KIRP, a renal cancer closely related to RCC [30]. B3GALT1 is involved in the biosynthesis of the carbohydrate moieties of glycolipids and glycoproteins, and has been found to be involved in cervical adenosquamous carcinoma [31].…”
Section: Discussionmentioning
confidence: 99%